Inside Back Cover: Electrochemical Behavior of Gold–Silver Alloy Nanoparticles (ChemElectroChem 7/2016). Issue 7 (27th June 2016) - Plowman, Blake J.; Sidhureddy, Boopathi; Sokolov, Stanislav V.; Young, Neil P.; Chen, Aicheng; Compton, Richard G.
Abstract : The Inside Back Cover picture shows the electrochemical behavior of Ag–Au alloy nanoparticles, providing insights into the electrochemical stability of such particles in chloride‐containing media and showing contrasting behavior to monometallic particles. More information can be found in the Communication by R. Compton and co‐workers onpage 1039 in Issue 7, 2016 (DOI:10.1002/celc.201600212 ).